Analisis Pemanfaatan Gas Alam sebagai Pengganti Gas LPG - Meilinda Suriani Harefa; Syukri Hidayat; Grace Mercy Epsilon Hia; Sabda Yanti Pasaribu; Natasya Kaila Putri; Mhd Asa Arzaki Muis (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
The use of natural gas to replace liquefied petroleum gas (LPG) is a strategic step to reduce dependence on imported energy and support a sustainable energy transition. The purpose of this study is to analyze the possibilities, challenges, and impacts of using natural gas as a source of household energy in Indonesia. The research method used is a qualitative approach that collects primary data through questionnaires and interviews with household users and secondary data from related magazines. The results of the study indicate that Indonesia has great potential in meeting energy needs because it is rich in natural gas reserves. From an economic perspective, the use of natural gas is cheaper than liquefied gas, especially in the long term. However, the main challenges are limited distribution infrastructure, lack of public awareness of the benefits of natural gas, and the need for regulations to support the implementation of this energy transition. The results are positive impacts such as reduced CO2 emissions, increased energy efficiency and savings in foreign exchange. In summary, the use of natural gas as a substitute for LPG is feasible, but requires strategic steps such as expanding natural gas infrastructure, educating the public, and strengthening the regulatory framework. This study recommends that the government, energy companies, and the community work together to ensure an effective and sustainable energy transition.